2019
DOI: 10.1016/j.buildenv.2018.10.044
|View full text |Cite
|
Sign up to set email alerts
|

A long-term dynamic model for predicting the concentration of semivolatile organic compounds in indoor environments: Application to phthalates

Abstract: Semivolatile organic compounds (SVOCs) in indoor environments can partition into the gas phase, airborne particles, and settled dust and onto available surfaces. A long-term dynamic model was developed to predict the hourly concentrations of SVOCs over a year in the gas phase, airborne particles, and settled dust and on each sink surface. The model takes into account mass transfer mechanisms, the reactivity of SVOCs with oxidants indoors, and the influence of four indoor environmental factors (the air temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…However, several studies observed different degrees of temporal variability of SVOC dust concentrations across chemical classes or within the same chemical class 18,31‐33 . Episodic occupant activities (eg, cooking, vacuuming, and ventilation) and environmental factors (eg, temperature, relative humidity, and airborne particulate matter concentration) are also known to affect SVOC air and/or dust concentrations during a short period of time 34,35 . Seasonal factors (eg, different product use pattern and ventilation frequency) may also play a role in temporal variability in measured dust concentrations 36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies observed different degrees of temporal variability of SVOC dust concentrations across chemical classes or within the same chemical class 18,31‐33 . Episodic occupant activities (eg, cooking, vacuuming, and ventilation) and environmental factors (eg, temperature, relative humidity, and airborne particulate matter concentration) are also known to affect SVOC air and/or dust concentrations during a short period of time 34,35 . Seasonal factors (eg, different product use pattern and ventilation frequency) may also play a role in temporal variability in measured dust concentrations 36 .…”
Section: Introductionmentioning
confidence: 99%
“…18,[31][32][33] Episodic occupant activities (eg, cooking, vacuuming, and ventilation) and environmental factors (eg, temperature, relative humidity, and airborne particulate matter concentration) are also known to affect SVOC air and/or dust concentrations during a short period of time. 34,35 Seasonal factors (eg, different product use pattern and ventilation frequency) may also play a role in temporal variability in measured dust concentrations. 36 Thus, further studies are needed to extensively examine temporal variability of dust concentrations for a wide range of SVOCs detected in household dust and other determinants (eg, chemical properties, seasonal difference in use patterns, or emission sources) of the temporal variability of dust concentrations.…”
mentioning
confidence: 99%
“…The higher temperature could increase the emission rate of plasticizer, so higher PAEs concentrations in dust have also been attributed to electronic devices, cosmetics and personal care products. 39,40 Therefore, putting the computer in children's room and using mosquito-repellent incense were also important factors for BP neural network establishment. The association analysis can also provide a reference for reducing indoor PAEs concentration.…”
Section: A Comparison Of the Effectiveness Of Different Interventionsmentioning
confidence: 99%
“…If it is assumed that a linear equilibrium relationship exists between the settled dust and the gas layer directly adjacent to the source material (SI Section 3), the critical parameters for modeling emission into dust are y 0 , h m (SI Section IV), the dust/air partition coefficient K dust (SI Section VI), the particle deposition velocity v d , and the concentration of airborne particles, which is usually given as total suspended particles, TSP. ,,, Instead of TSP, other particle concentration ranges such as PM 2.5 can be used, depending on the research question. , …”
Section: A Framework For Predicting Exposure To Indoor Svocsmentioning
confidence: 99%